2018
DOI: 10.1111/ajt.14645
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil derived CSF1 induces macrophage polarization and promotes transplantation tolerance

Abstract: Summary The colony-stimulating factor 1 (CSF1) regulates the differentiation and function of tissue macrophages and determines the outcome of the immune response. The molecular mechanisms behind CSF1-mediated macrophage development remain to be elucidated. Here we demonstrate that neutrophil-derived CSF1 controls macrophage polarization and proliferation, which is necessary for the induction of tolerance. Inhibiting neutrophil production of CSF1 or preventing macrophage proliferation, using targeted nanopartic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 40 publications
1
55
0
1
Order By: Relevance
“…For example, in an experimental model of heart transplantation, organ acceptance was described to be dependent on macrophage colony stimulating factor-1 activation of macrophages, with neutrophils identified as the main source of colony stimulating factor-1. 59 In this study, the authors used S100A8cre x colony stimulating factor-1 floxed mice to deplete colony stimulating factor-1 specifically within neutrophils and observed that the organ infiltrating macrophages failed to acquire a prorepair phenotype. 59 In the context of infection-induced injury, the role of neutrophil-macrophage crosstalk in tissue repair has been reported by a recent publication investigating helminth infection.…”
Section: Cytokines and Growth Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in an experimental model of heart transplantation, organ acceptance was described to be dependent on macrophage colony stimulating factor-1 activation of macrophages, with neutrophils identified as the main source of colony stimulating factor-1. 59 In this study, the authors used S100A8cre x colony stimulating factor-1 floxed mice to deplete colony stimulating factor-1 specifically within neutrophils and observed that the organ infiltrating macrophages failed to acquire a prorepair phenotype. 59 In the context of infection-induced injury, the role of neutrophil-macrophage crosstalk in tissue repair has been reported by a recent publication investigating helminth infection.…”
Section: Cytokines and Growth Factorsmentioning
confidence: 99%
“…59 In this study, the authors used S100A8cre x colony stimulating factor-1 floxed mice to deplete colony stimulating factor-1 specifically within neutrophils and observed that the organ infiltrating macrophages failed to acquire a prorepair phenotype. 59 In the context of infection-induced injury, the role of neutrophil-macrophage crosstalk in tissue repair has been reported by a recent publication investigating helminth infection. Larval migration through the lungs of infected mice results in the rapid recruitment of neutrophils and leads to tissue damage and hemorrhaging during the acute phase of infection.…”
Section: Cytokines and Growth Factorsmentioning
confidence: 99%
“…These analyses showed a predominance of Ly6C lo cells with similar elevated ratios of Ly6C lo :Ly6C hi C5ar1 fl/fl WT and C5ar1 fl/fl xLysM‐cre Ly6C lo cells within the graft‐infiltrating myeloid cells, indicating conversion is unaffected by C5aR1 expression. In addition, while neutrophil‐produced CSF1 binding to CSF1 receptor (CSF1‐R) on Ly6C hi myeloid cells is required for conversion to the Ly6C lo regulatory phenotype, we did not detect differences in either CSF1 gene expression (Figure G) or CSF1‐R surface expression on graft‐infiltrating mononuclear cells between allografts in control C5ar1 fl/f versus C5ar1 fl/fl x LysM‐cre allograft recipients (Figure H‐I).…”
Section: Resultsmentioning
confidence: 78%
“…The protolerogenic immune mechanisms initiated by costimulatory blockade are incompletely understood, but experimental evidence supports the induction and maintenance of donor‐reactive regulatory T cells (Tregs) as crucial . Studies published since 2008 have additionally implicated a subset of regulatory myeloid cells (Mregs) as important contributors to costimulatory blockade‐induced transplant survival . Myeloid cells capable of suppressing T cell immunity, sometimes referred to as myeloid‐derived suppressor cells (MDSCs), were initially observed in tumor systems and were shown to inhibit anti‐tumor T cell immunity.…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophils rapidly sense inflammatory mediators and migrate to sites of infection, then employ phagocytosis, degranulation, and reactive oxygen species to destroy pathogens. In addition to inducing the inflammatory response, neutrophils also regulate the function of other immune cells through the secretion of soluble signaling molecules . In recent studies, biomaterials were designed to mimic two key neutrophil features: the ability to generate inflammatory mediators and the ability to migrate quickly to sites of infection .…”
Section: Biomaterials Enable Analysis Of Immune Signaling Through Conmentioning
confidence: 99%